Hubungan Tingkat Pengetahuan Ibu Hamil terhadap Perilaku Pencegahan HIV di Puskesmas Cilacap Selatan II Kabupaten Cilacap - Sri Murwani Nuraini; Alfi Noviyana (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
The high prevalence of HIV/AIDS in Indonesia, including 2,490 positive cases among pregnant women in 2023, highlights the importance of prevention efforts, particularly in preventing mother-to-child transmission. At Puskesmas Cilacap Selatan II, one out of 265 pregnant women tested between January and October 2024 showed a reactive HIV result. Early detection and pregnant women’s knowledge are crucial, as low knowledge can hinder the utilization of Voluntary Counseling and Testing (VCT) services. This study aimed to analyze the correlation between pregnant women’s knowledge and HIV prevention behaviors. Using a quantitative correlational method with a cross-sectional design, 86 respondents were selected from a population of 341 through purposive sampling. Data were collected via questionnaires and analyzed using a correlation test (specific statistical test to be confirmed). The results showed a p-value of 0.001 (<0.05) and a correlation coefficient of 0.765, indicating a very strong and positive correlation—the higher the knowledge, the better the prevention behavior. It was concluded that pregnant women’s knowledge is strongly associated with HIV prevention behavior. Therefore, it is recommended that the Puskesmas enhance HIV/AIDS education to prevent mother-to-child transmission.